2012
DOI: 10.1080/10810730.2011.650823
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Consumer Health Information on the Internet: A Comparison of U.S. Government–Funded and Commercially Funded Websites

Abstract: The Internet has become an extremely prevalent means of communicating health information to consumers. Guidelines for selecting reliable health information websites give preference to U.S. government sites over commercially funded sites. However, these websites are not useful to consumers unless they are able to read and understand them. The authors' objective was to compare the readability of Internet health information intended for consumers found on U.S. government-funded websites versus that found on comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 12 publications
1
30
2
Order By: Relevance
“…Moreover, EHIA written by for-profit entities, many of whom were advocating e-cigarettes, were significantly easier to read than materials written by nongovernment organizations, non-US government entities, and the US government. Our results contrast with the results of a previous readability study comparing health information written by commercially funded sources and government-funded sources [18]. However, both studies found that the readability of health information was generally too difficult for the public.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, EHIA written by for-profit entities, many of whom were advocating e-cigarettes, were significantly easier to read than materials written by nongovernment organizations, non-US government entities, and the US government. Our results contrast with the results of a previous readability study comparing health information written by commercially funded sources and government-funded sources [18]. However, both studies found that the readability of health information was generally too difficult for the public.…”
Section: Discussioncontrasting
confidence: 99%
“…To assess readability (ie, the estimated US grade level that is required to comprehend a text), we used Flesch-Kincaid grade level [22], Simple Measure Of Gobbledygook (SMOG) Index [23], Coleman and Liau Index [24], and automated readability index [25], which are widely used metrics in previously mentioned readability studies [10-16,18]. To perform the automated readability analysis, we used the open-source Python textstat package [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, more than 20% of social network users keep track of updates or their online friends’ health experiences on network sites, 11% post medical queries, and 9% join a health-related group on a media site 79 . Moreover, it has been shown that even medical students are more inclined to use social network pages on influenza vaccination in an informal language, 80 rather than the highly technical language that is often used by the websites of official health authorities 81 . The above considerations indicate that social network sites are potentially efficacious in delivering vaccination and health promotion messages to teenagers.…”
Section: Web 20 Applicationsmentioning
confidence: 99%
“…Resources with broad coverage of rare genetic disorders include OMIM, GeneTests, and OrphaNet. These sites provide information for research professionals but have limited content for the general public [19,20]. The challenge posed to rare disease communities is enormous.…”
Section: Introductionmentioning
confidence: 99%